The prevalence of olfactory dysfunction and its associated factors in patients with COVID-19 infection: A Hospital-based study (Bangladesh Journal of Medical Science, 2023)
Background: The coronavirus disease of 2019 (COVID-19) is a global viral pandemic that originated in East Asia (China) and is quickly spreading to every corner of the globe. In Bangladesh, no research has been conducted on olfactory dysfunction in COVID-19 infected patients and its associated factors. We aimed to determine the correlation between olfactory dysfunction (OD), particularly anosmia and COVID-19 infected patients’ demographic and clinical characteristics.Methods: We conducted a hospital based prospective observational study. We collected patients’ information, including laboratory-confirmed COVID-19 test results from a COVID dedicated hospital, Square Hospitals Ltd., Dhaka, Bangladesh. We used the Pearson Chi-square test and logistic regression model to assess the associations between demographic and clinical characteristics and OD (i.e. anosmia).Results: Out of 600 COVID-19 positive patients, 38.7% were diagnosed with OD. We found that patients’ age, smoking status, cough, dyspnea, sore throat, asthenia, and nausea or vomiting were significantly associated with anosmia. We observed smoking patients were 1.73 times more likely to experience anosmia than non-smoking patients Odd ratio (OR)=1.73, 95% confidence interval (CI) = 1.01-2.98]. Interestingly, our data showed that the risk of developing anosmia was greater in younger patients than in older patients, and this risk decreased as age increased (OR) range for different age groups: 1.26 to 1.08]. In addition, patients who complained of asthenia had a significantly double risk of developing anosmia [OR = 1.96, CI = 1.23-3.06].Conclusions: Our study shows that 38.7% of patients diagnosed with OD. Patients’ age, smoking status, and asthenia are significantly positively associated with anosmia. Since anosmia can be a significant marker for the diagnosis of COVID-19, we suggest regular screening of OD in patients with early symptoms of COVID-19, particularly younger patients, smokers, and who complained of asthenia.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 195-204